Semantic Volte Face of English Words in Nepal - Dewan, Shankar (KMC Journal, 2023)
With the spread of English globally and its contact with the local languages, English words have undergone some changes in their pronunciation, forms, meanings, and functions. This paper attempted to explore the changes in the meaning of English words in Nepal. From different literary texts, I purposively selected thirty English words that I found unique in their meanings, four English language teachers who could provide information about the semantic changes of some English words, and my own experiences. The selected words were categorized into five themes: semantic broadening, semantic narrowing, amelioration, pejoration, and semantic shifts, which were then analyzed and interpreted. The study reveals that English words in Nepal have changed their meanings from narrow to broad, from positive to negative and vice versa, and to something different or new in meanings, which are the variety markers of Nepali English (NE). The results of the study are useful for teaching profession, World Englishes, corpus linguistics, contact linguistics, contact literature, semantics, and pragmatics.